2022
DOI: 10.3390/ijerph19095550
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity Levels and Eating Behaviours during the COVID-19 Pandemic: Sociodemographic Analysis in University Students

Abstract: The COVID-19 pandemic has forced schools and universities to shift their activities online, influencing the adoption of health-related behaviours such as physical activity and healthy dietary habits. The present study investigates the changes in adherence to a healthy diet and regular physical activity in university students in Italy before and during the COVID-19 pandemic and understands the role of sociodemographic variables in creating the changes above. We conducted a repeated cross-sectional survey perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 87 publications
0
16
0
4
Order By: Relevance
“…As reported by several studies, self-control over eating can be particularly weak at times of increased psychological tension and distress, including collective distress, as may have occurred during the current pandemic, where social constraints have also often reinforced sedentary lifestyles in young adults, fostering unregulated and compensatory eating behaviors ( Diotaiuti et al, 2021b ; Cavicchiolo et al, 2022 ; Ferrara et al, 2022 ; Galli et al, 2022 ), and even addictive practices ( Petruccelli et al, 2014 ; Avena et al, 2021 ; Lim, 2021 ; Diotaiuti et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As reported by several studies, self-control over eating can be particularly weak at times of increased psychological tension and distress, including collective distress, as may have occurred during the current pandemic, where social constraints have also often reinforced sedentary lifestyles in young adults, fostering unregulated and compensatory eating behaviors ( Diotaiuti et al, 2021b ; Cavicchiolo et al, 2022 ; Ferrara et al, 2022 ; Galli et al, 2022 ), and even addictive practices ( Petruccelli et al, 2014 ; Avena et al, 2021 ; Lim, 2021 ; Diotaiuti et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(44), in which PA was significantly reduced in young adults during the pandemic. Studies have also found that young adults did not return to pre-pandemic PA levels, which was characterized by a combination of increased sedentary activity and a lower frequency of PA bouts (45). By the time of the follow-up assessment, both CT and PCOV increased moderate PA levels to satisfy CDC PA standards where CT presented with a median of 33.72 min/day (236.04 min/wk) of moderate PA and PCOV increased to a median of 27.86 min/day (195.02 min/wk) of moderate PA.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), by 2022 chronic diseases will account for 71% of the total number of deaths per year, with the percentage increasing in recent years in countries with fewer economic resources. Evidence suggests that chronic diseases are one of the greatest challenges facing health systems worldwide and they are strongly associated with several modifiable risk factors, notably physical inactivity, sedentary lifestyles and poor lifestyle habits ( Anderson and Durstine, 2019 ; Ferrara et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%